From Risk-Seeking to Risk-Averse: The Development of Economic Risk Preference from Childhood to Adulthood - Paulsen, David J.; Platt, Michael L.; Huettel, Scott A.; Brannon, Elizabeth M. (Frontiers in Psychology, 2012)
Adolescence is often described as a period of heightened risk-taking. Adolescents are notorious for impulsivity, emotional volatility, and risky behaviors such as drinking under the influence of alcohol. By contrast, we found that risk-taking declines linearly from childhood to adulthood when individuals make choices over monetary gambles. Further, with age we found increases in the sensitivity to economic risk, defined as the degree to which a preference for assured monetary gains over a risky payoff depends upon the variability in the risky payoff. These findings indicate that decisions about economic risk may follow a different developmental trajectory than other kinds of risk taking, and that changes in sensitivity to risk may be a major factor in the development of mature risk aversion.